2019
DOI: 10.1155/2019/1064793
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol 7-O-Glucoside Herbacitrin Inhibits HIV-1 Replication through Simultaneous Integrase and Reverse Transcriptase Inhibition

Abstract: Here we report the evaluation of the antiretroviral effect of two flavonoid 7-O-glucosides, herbacitrin (1) and gossypitrin (2), together with quercetin (3), a well-studied flavonol. Antiviral activity of the flavonoids was assessed by analyzing HIV-1 p24 core protein levels in the supernatants of HIV-1 infected MT-4 and MT-2 cell cultures. The compounds showed mild to weak cytotoxic activities on the host cells; herbacitrin was the strongest in this regard (CC50=27.8 and 63.64 μM on MT-4 and MT-2 cells, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
7
0
4
Order By: Relevance
“…Quercetin has been investigated in vitro as an antiviral agent for HIV due to its ability to inhibit crucial enzymes: reverse transcriptase (RT), integrase (IN), and protease (PR) (80). Quercetin significantly reduces HIV viral replication (81) and, when added to peripheral blood mononuclear cells (PBMNc) infected with HIV and compared to HIV infected controls, quercetin reduced the levels of p24, Long Terminal Repeat (LTR) gene expression, and viral infectivity together with an inhibition of TNF-α and upregulation of IL-13 (11).…”
Section: Inhibition Of Reverse Transcriptasementioning
confidence: 99%
“…Quercetin has been investigated in vitro as an antiviral agent for HIV due to its ability to inhibit crucial enzymes: reverse transcriptase (RT), integrase (IN), and protease (PR) (80). Quercetin significantly reduces HIV viral replication (81) and, when added to peripheral blood mononuclear cells (PBMNc) infected with HIV and compared to HIV infected controls, quercetin reduced the levels of p24, Long Terminal Repeat (LTR) gene expression, and viral infectivity together with an inhibition of TNF-α and upregulation of IL-13 (11).…”
Section: Inhibition Of Reverse Transcriptasementioning
confidence: 99%
“…It was shown that herbacitrin inhibits both RT and integrase in HIV-1 infected MT-4 and MT-2 cell cultures, resulting in viral replication blockade at different stages. At a concentration of 21.5 µg/M, herbacitrin could suppress RT activity, while it could inhibit integrase at a lower concentration, 2.15 µM [ 77 ]. Scutellarin purified from Erigeron breviscapus is a flavonoid with anti-HIV-1 activity.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in the aerial parts of the plant, alkanes (90-101), alcohols (102-107), aldehydes (108)(109)(110)(111)(112)(113), ketones (114,115) α-tocopherol (116), carboxylic acids (117,118) and sugars (119,121) were also identified (Table 4). Several of these metabolites change their concentrations in relation to the three phenological stages of the plant (preflowering, flowering and postflowering).…”
Section: Phenolic and Carboxylic Acid Compoundsmentioning
confidence: 99%
“…These activities are crucial for viral replication, and therefore they represent important drug targets for which there is a need for new drugs. All the extracts possessed anti-HIV activity and among them, ethanolic extracts were more active than aqueous extracts, and the ethanolic extract from flowers seemed to be the most effective inhibitor of HIV-1 RT-associated RNA-dependent DNA polymerase and Ribonuclease H. Among the compounds identified in flower and leaf ethanolic extracts of E. characias, compounds 74 , 78 , 81 , 84 and 89 showed documented HIV inhibitory activity [ 108 , 109 , 110 , 111 ].…”
Section: Biological Activitiesmentioning
confidence: 99%